"This one is stronger". Spotlights on the lifelong learning professional-in-action - Josje van der Linden (Journal of Social Intervention: Theory and Practice, 2016)
ABSTRACT“This one is stronger.” Spotlights on the lifelong learning professional-in-action Around the world, lifelong learning is being promoted as a strategy for coping with the changing realities of life and work. The fourth Sustainable Development Goal, agreed in September 2015, reflects this: “ensure equitable and inclusive quality education and promote lifelong learning opportunities for all”. Despite its importance, doubts remain about the implementation of this goal in practice (Van der Kamp, 2000; Regmi, 2015). This article looks at the practice of lifelong learning from the point of view of the professionals involved, their actions and the way these actions are challenged, supported and further developed. Following Schön’s “reflection-in-action” (1983), the term “professional-in-action” is used to stress the role of the professional in making the difference on the ground. The leading question is: how can lifelong learning professionals be supported in their contribution to surrounding society and its citizens? The professionals-in-action featured in this article include professionals based in the Netherlands as well as in other, less privileged contexts. Meaningful experiences are used to build a story about challenges, the right to exist, commitment, recognition and room to manoeuvre. The experiences reveal the importance of interacting with the learner and the professional space that is necessary to achieve this. Professionalization in professional learning communities and practice-oriented research must accompany this professional space. SAMENVATTING“Deze is sterker”. Spotlights op de leven lang leren professional-in-actieOm te kunnen omgaan met de veranderende realiteit in leven en werk, wordt wereldwijd een leven lang leren aangemoedigd. Het vierde duurzame ontwikkelingsdoel, vastgesteld in september 2015, weerspiegelt dit: “het verzekeren van kwalitatief goed onderwijs en het bevorderen van de mogelijkheden om een leven lang te leren voor iedereen”. Ondanks het belang van dit doel, is er twijfel over de uitvoerbaarheid in de praktijk (Van der Kamp, 2000; Regmi, 2015). Dit artikel gaat in op de praktijk van een leven lang leren vanuit het perspectief van de professionals, hun acties en de ondersteuning en ontwikkeling daarvan. In navolging van Schön's “reflectie-in-actie” (1983), wordt de term “professional-in-actie” gebruikt om de rol van de professional in de praktijk van een leven lang leren te benadrukken. Leidende vraag is hoe professionals kunnen worden ondersteund in hun bijdrage aan de omringende samenleving en haar burgers. De professionals-in-actie in dit artikel omvatten professionals in de Nederlandse context, maar ook in andere, minder geprivilegieerde contexten. Betekenisvolle ervaringen worden gebruikt om een betoog op te bouwen over de uitdagingen, het recht van bestaan, de betrokkenheid, erkenning en professionele ruimte. De ervaringen tonen het belang van interactie met de deelnemers en de professionele ruimte om daar invulling aan te geven. Deze professionele ruimte dient gepaard te gaan met professionalisering in professionele leergemeenschappen en praktijkgericht onderzoek.